2016
DOI: 10.14737/journal.aavs/2016/4.7.357.362
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Protein Levels in Diet on Production and Emissions in WLH Layer

Abstract: | The present study was conducted to evaluate the effect of various levels of protein, in the diets of WLH layers, on production performance and on nitrogen (N) and phosphorus (P) levels in the excreta. The trial was conducted in a total of 108 WLH layers (BV-300) at 25 weeks of age. The birds were allocated into three dietary treatment groups; six replicates of six hens per group. Diets with 2700 Kcal/kg of metabolizable energy (ME)and a constant ratio between digestible Methionine+Cystine (M+C), Threonine (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
2
1
0
Order By: Relevance
“…Neither DFI nor daily energy intake were been affected by dietary CP levels studied (Table , 2). This result was agreed with the findings by Kumari et al (2016) who found that increasing protein content of the diet resulted in increases in the body weight. In the same trend Yakout (2010) indicated that the best value of body weight gain was obtained by layers fed high-CP diets.…”
Section: Resultssupporting
confidence: 93%
“…Neither DFI nor daily energy intake were been affected by dietary CP levels studied (Table , 2). This result was agreed with the findings by Kumari et al (2016) who found that increasing protein content of the diet resulted in increases in the body weight. In the same trend Yakout (2010) indicated that the best value of body weight gain was obtained by layers fed high-CP diets.…”
Section: Resultssupporting
confidence: 93%
“…In respect of protein, our results were consistent with those of Kumari et al (2016), who noticed that a diet high in protein increased body weight. Also, Alagawany et al (2020) found that the hens fed an 18% CP diet had the best final BW and BWC values compared with those fed 16% protein content.…”
Section: Table (2): Effect Of Dietary Energy Levels Protein Levels An...supporting
confidence: 92%
“…Among other reasons, this is driving the urge to find alternatives for imported soybean meal in poultry diets. Besides that, the emission of nutrients such as nitrogen and phosphorus via the poultry manure contributes to the environmental impact of the poultry production (Kumari et al, 2016).…”
mentioning
confidence: 99%